Kedudukan Bukti Audit Kerugian Keuangan Negara dalam Penetapan Tersangka Tindak Pidana Korupsi - M. Agam Ramadansyah Irawan (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Audit reports on the calculation of state financial losses still do not have a definite position within the evidentiary system of Indonesian procedural law. Although the elucidation of Article 238 paragraph (2) of the Criminal Procedure Code (KUHAP) recognizes financial auditors as experts, this provision has not fully provided legal certainty. Uncertainty remains regarding what is recognized by KUHAP as evidence, namely whether the audit report itself or the auditor’s testimony presented in court as an expert witness. This issue also has implications for whether the designation of a suspect in a corruption case must be supported by an audit report on state financial losses. This study employs a normative legal research method with a statutory approach. The findings indicate that, in order to achieve legal certainty, audit reports on state financial losses should be categorized as documentary evidence. This is because such reports are written documents that explain a particular matter based on the expertise of an auditor. The element of causing losses to state finances cannot be proven without an audit report on state financial losses. Designating a suspect without evidence in the form of an audit report on state financial losses may undermine the principle of due process of law, as a person is accused of causing losses to state finances while the act resulting in such losses has not yet been proven.